PENGEMBANGAN MEDIA KARTU KATA BERGAMBAR UNTUK MELATIH KEMAMPUAN MEMBACA PERMULAAN PADA SISWA KELAS 1 SDN KARANGSONO 3 MRANGGEN DEMAK - Erlangga Reza Rahmandhani; Duwi Nuvitalia; Rofian (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Early reading ability is a crucial foundation in developing basic literacy skills among elementary school students However, a preliminary study conducted at SDN Karangsono 3 Mranggen Demak revealed that most first-grade students still experience difficulties in recognizing letters, forming syllables, and reading simple words. This issue is related to the use of conventional teaching methods that do not actively engage students in the learning process. This study aims to develop illustrated word card media as an alternative learning tool that is both enjoyable and effective in improving early reading skills The research employed a Research and Development (R&D) approach using the ADDIE model, which consists of the stages of Analysis, Design, Development Implementation, and Evaluation The research subjects were 22 first-grade students and one classroom teacher. Data were collected through interviews, observations, expert validation questionnaires and field trials. The results showed that the illustrated word card media was categonzed as highly feasible, with validation scores of 95.5% from media experts, 98 2% from material experts, 89.2% from teachers, and 94 5% from students. The classroom implementation demonstrated increased enthusiasm, engagement, and students reading abilities. Therefore, the developed illustrated word card media is proven to be effective, practical, and suitable for enhancing early reading skills in lower-grade elementary school students